Copy number variation in potato – an asexually propagated autotetraploid species. (13th May 2013) - Iovene, Marina; Zhang, Tao; Lou, Qunfeng; Buell, C. Robin; Jiang, Jiming
Summary: Copy number variation (CNV) has been revealed as a significant contributor to the genetic variation in humans. Although CNV has been reported in several model animal and plant species, the presence of CNV and its biological impact in polyploid species has not yet been documented. We conducted a fluorescence in situ hybridization (FISH)‐based CNV survey in potato, a vegetatively propagated autotetraploid species (2 n  = 4x = 48). We conducted FISH analysis using 18 randomly selected potato bacterial artificial chromosome (BAC) clones in a set of 16 potato cultivars with diverse breeding backgrounds. Six BACs (33%) with insert sizes of 137–145 kb were found to be associated with large CNV events detectable at the cytological level. We demonstrate that the large CNVs associated with two specific BACs (RH102I10 and RH83C08) were widespread among potato cultivars developed in North America and Europe. We measured the transcript abundance of four genes associated with the CNV spanned by BAC RH102I10. All four genes displayed a dosage effect in transcription. Although potato is vegetatively propagated, we observed that female gametes lacking the RH102I10‐associated CNV were inferior to those with at least one copy of this CNV, indicating that the RH102I10‐associated CNV can impact on the growth and development of the potato plants. Our results show that CNV is highly abundant in the potato genome and may play a significant role in genetic variation of this important food crop.